SCREENING FOR CLAUSTROPHOBIA IN MRI – A PILOT STUDY - Lisa, Booth; Lois, Bell (European Scientific Journal, ESJ, 2013)
Purpose- Claustrophobia during MRI examinations still presents a significant burden for patients and the NHS. Despite many strategies being suggested to reduce this burden, many are not routinely practiced due to questions over their cost-effectiveness. One way to ensure that strategies are cost effective is to screen for those patients who are most likely to experience difficulties during the examination. Method – This pilot study utilised the Claustrophobia Questionnaire (CLQ) to determine its predictive qualities in screening for claustrophobia in MRI. A retrospective sample of patients who withdrew from the MRI examination (citing claustrophobia as the cause) were cross matched against a population who were able to tolerate the exam. Results – The results were analysed using Mann Whitney and demonstrated a significant difference in the scores between those who could tolerate the MRI environment and those who could not. Conclusion – The CLQ may be a valid tool for screening those patients who may be unable to tolerate MRI examinations prior to attendance, enabling strategies to be targeted to this particular group.